2006
DOI: 10.1210/jc.2006-0430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Intrauterine Device on the Gene Expression Profile of the Endometrium

Abstract: Our results reveal that a refractory endometrium in a fertile woman produced by an IUD is induced by preventing the normal transition to a receptive gene expression profile through effects on a specific subset or cluster of genes that impact on endometrial receptivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 27 publications
0
35
1
1
Order By: Relevance
“…Indeed, changes in gene expression are not necessarily reflected in changes in translated proteins, nor does gene analysis take into account posttranscriptional, translational, or posttranslational changes that relate to cyclical transitions. Of the hundreds of gene expression changes typically identified by microarray, relatively few are common to more than two studies [47,48]. Comparison of proteomic data with published gene expression data in similar cohorts of women [47,49,50] also have revealed an overall lack of correlation between the two, suggesting that posttranscriptional or translational regulation is an important feature in human biology.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, changes in gene expression are not necessarily reflected in changes in translated proteins, nor does gene analysis take into account posttranscriptional, translational, or posttranslational changes that relate to cyclical transitions. Of the hundreds of gene expression changes typically identified by microarray, relatively few are common to more than two studies [47,48]. Comparison of proteomic data with published gene expression data in similar cohorts of women [47,49,50] also have revealed an overall lack of correlation between the two, suggesting that posttranscriptional or translational regulation is an important feature in human biology.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experimental procedures were approved by the Institutional Animal Care and Use Committee of Obihiro University (no. [18][19][20][21][22][23][24][25]. Twelve Holstein cows (3-7 yr of age) that had been ovariectomized 40 -50 days before the beginning of the experiment were maintained in a free-stall barn throughout the experimental period and had free access to food and water.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in mRNA expression profiles in bovine endometrium during the estrous cycle were already evaluated in two studies (7,36). Microarray studies that give an insight into the changes occurring in gene expression in the endometrium during the sexual cycle have been performed also in humans (19), mice (26), sheep (12), and pigs (44). In cattle, two studies (8,28) have taken two different animal model approaches to address the differences in endometrial gene expression between pregnant and cycling animals on day 18.…”
mentioning
confidence: 99%
“…In the present study, the presence of the IUD had no significant effect on LIF expression in the endometrium. Horcajadas et al [19] investigated the expression of 147 genes in the endometrium of five females prior to IUD insertion, with the IUD in place and after IUD removal. The study found a significant decline in LIF expression with an IUD in place and 2 months after IUD removal compared to expression prior to IUD insertion.…”
Section: Discussionmentioning
confidence: 99%